2012
DOI: 10.1111/j.1365-2826.2012.02294.x
|View full text |Cite
|
Sign up to set email alerts
|

Gonadal Steroid Induction of Kisspeptin Peptide Expression in the Rostral Periventricular Area of the Third Ventricle During Postnatal Development in the Male Mouse

Abstract: Kisspeptin and its G-protein coupled receptor Gpr54 are essential for the pubertal activation of gonadotrophin-releasing hormone (GnRH) neurones, with Gpr54 mutation or deletion resulting in failed puberty and infertility in humans and mice. The number of kisspeptin-immunoreactive neurones in the rostral periventricular area of the third ventricle (RP3V) increases during pubertal development in concert with the appearance of kisspeptin appositions with GnRH neurones in the mouse rostral preoptic area. We recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 48 publications
0
15
1
Order By: Relevance
“…The developmental profile of kisspeptin mRNA obtained in our study with real-time PCR is in agreement with previous data [44] and well coincides with immunohistochemical identification of kisspeptin expression. During the first 2 weeks of life, low-level immunoreactivity for kiss-1 was detected in the male rat arcuate nucleus [45]. Though mice lacking kisspeptin-Kiss1r signaling had smaller testes already at postnatal day 10 [21], kisspeptin or its receptor mRNA levels in the present study did not correlate with testis weights during the periods of the proportional and accelerated growth of the gonads.…”
Section: Discussioncontrasting
confidence: 78%
“…The developmental profile of kisspeptin mRNA obtained in our study with real-time PCR is in agreement with previous data [44] and well coincides with immunohistochemical identification of kisspeptin expression. During the first 2 weeks of life, low-level immunoreactivity for kiss-1 was detected in the male rat arcuate nucleus [45]. Though mice lacking kisspeptin-Kiss1r signaling had smaller testes already at postnatal day 10 [21], kisspeptin or its receptor mRNA levels in the present study did not correlate with testis weights during the periods of the proportional and accelerated growth of the gonads.…”
Section: Discussioncontrasting
confidence: 78%
“…While cell numbers in the RP3V of male rodents are much lower than that for females (discussed below), Han et al (13) showed that the number of cells expressing kisspeptin mRNA was greater in adults than juveniles and that expression level per cell increased as well. Clarkson and Herbison (11) reported that kisspeptin-positive cell numbers began to increase at PND 25 and peaked at PND 45, but these changes may reflect increased circulating levels of gonadal steroids since they were abolished by gonadectomy at PND 20 and restored to normal with either testosterone or estradiol treatment (138). In contrast, others have reported very low cell numbers with no change (50;126) or only small changes (128) in the RP3V.…”
Section: 5 Development and Sex Differences In The Kisspeptin Signalmentioning
confidence: 99%
“…One explanation is that wildtype males are not exposed to increasing testosterone (converted to estradiol) during the postnatal period from P2 to P28. The testosterone surge (1.6–1.7 ng/mL) at 1–2 hours after birth is followed by a drop in the level of testosterone (0.04 to 0.6 ng/mL) on days P2-P30 [31, 32, 34]. The increase in testosterone starts about P35 (0.9 ng/mL) and continues to rise by P40 (2.1 ng/mL), which is early puberty for males.…”
Section: Discussionmentioning
confidence: 99%